Comparison of the Efficacy of Different Schemes for Using Recombinant Vector Vaccines against Ebola Fever, Based on Vaccinia Virus, MVA Strain - L. F. Stovba; O. V. Chukhralya; D. I. Pavel’ev; N. K. Chernikova; S. V. Borisevich (Проблемы особо опасных инфекций, 2024)
The aim of this review was to investigate the use of the vaccines based on vaccinia virus, MVA stain, and adenovirus vectors for the prevention of Ebola virus disease. The recombinant MVA strains expressing antigen determinants of Filoviridae family representatives were assessed as possible candidates for vaccine preparations. Application of this virus as a vaccine vector is conditioned by the absence of herd immunity to smallpox and its safety for healthy adult volunteers, children, adolescents, individuals suffering from tuberculosis, persons aged 56–80 years, people with diagnosed atopic dermatitis, AIDS. Furthermore, immunization with the vaccine on the basis of vaccinia virus, MVA strain, does not cause complications associated with cardiovascular diseases. Preclinical trials on immunogenicity and protective efficiency were carried out on immune-competent and immune-compromised mice; guinea pigs adapted to Ebola virus; rhesus macaques and cynomolgus monkeys. Presented are the results of experiments on the creation of vaccines expressing either only viral glycoprotein or viral glycoprotein and structural protein Vp40. Given that Ebola fever and other filovirus infection outbreaks are hard to predict, multivalent vaccines that would be able to provide protection against all filovirus species were designed. Clinical trials on simultaneous use of the vaccines based on recombinant adenovirus vectors and MVA strain showed more pronounced safety of vaccines on the basis of recombinant MVA strain. Studies of humoral and T-cell immune responses have revealed that this vector is more suitable for booster vaccination in case of heterologous prime/booster immunization scheme. Vaccination regimens for forming strong durable immune responses have been analyzed. Epidemiological modeling provided evidence that preventive immunization leading to long-term immunity in healthy population in areas of high epidemic risk will be of greater benefit in terms of controlling future outbreaks compared to ring immunization that was effective during smallpox eradication campaign. Increased immunity level, induced by prime/booster vaccination, persisting for a long period of time, will have an advantage over accelerated ring immunization; when the duration of protection is more significant than the speed it is formed at.